Chemical Composition of lavender and origano Essential Oil and Antifungal Action Against Penicillium expansum and Botrytis cinerea Fungi in Vitro (Damascus University Journal of agriculture sciences, 2024)
This study were conducted 2021 at Department of Plant Protection, in Faculty of Agriculture, Damascus University. In the present work, chemical composition of essential oil of lavender (Lavandula angustifolia) and oregano (Origanum vulgare) (family: Lamiacea) from garden of Hama –Syria. was determined by Chromatography- Mass Spectrometry GC/MS.Lavender mixture of leaves and flowers and from leaves of oregano oils were isolated by hydrodistillation in agriculture college department of plant protection. The results showed that yield of lavender and oregano oils province were 3.25 and 1.82% (v/w), respectively. The 18 components were identified in Lavender oil and the main component as follow; Limonene (2.15%), Eucalyptol (1,8-Cineol) (14.56%), Linalool (31.35%), Champhor (9.38%) and Borneol (14.54%).Also, found, 16 components were identified in oregano oil and the main component as follow; para-Cymene (15.69%), γ-Terpinene (11.05%),1,8-Cineol (7.21%), Linalool (5.79%), Thymol (9.16%) and Carvacrol (20.30%).The antifungal action of  essential oils of  Lavender and Origano were tested in vitro against some important postharvest fungi (Penicillium expansum and   Botrytis cinerea ) on PDA. The results  indicated that the essentials oils of the tested plant gave the significant inhibition for grow the tested fungi compared with control. The oregano oil gave the highest inhibition to growth B. cinerea fungi, Where gave 100 %  inhibition to fungus at 300 ppm., and gave 95.23 %  inhibition to P. expansum fungus at the same concentrate. However, the lavender essential oil gave the lowest inhibition to growth of the tested fungi. Where didn’t gave 100 %  inhibition to P. expansum and B. cinerea at 300 ppm. It was clear that the higher concentrations of essential oil caused higher suppression.Finding from this study confirmed that lavender and oregano essential oil can be used as natural fungicides to control postharvest fungi, thus reducing dependence on the synthetic fungicides.
Keywords: Essentials Oil; GAS Chromatography; Fungi